Reinforcing the association between distal 1q CNVs and structural brain disorder: A case of a complex 1q43‐q44 CNV and a review of the literature. Issue 3 (7th February 2016) - Hemming, Isabel A.; Forrest, Alistair R. R.; Shipman, Peter; Woodward, Karen J.; Walsh, Peter; Ravine, David G.; Heng, Julian Ik‐Tsen
Abstract : Copy Number Variations (CNVs) comprising the distal 1q region 1q43‐q44 are associated with neurological impairments, structural brain disorder, and intellectual disability. Here, we report an extremely rare, de novo case of a 1q43‐q44 deletion with an adjacent duplication, associated with severe seizures, microcephaly, agenesis of the corpus callosum, and pachygyria, a consequence of defective neuronal migration disorder. We conducted a literature survey to find that our patient is only the second case of such a 1q43‐q44 CNV ever to be described. Our data support an association between 1q43‐q44 deletions and microcephaly, as well as an association between 1q43‐q44 duplications and macrocephaly. We compare and contrast our findings with previous studies reporting on critical 1q43‐q44 regions and their constituent genes associated with seizures, microcephaly, and corpus callosum abnormalities [Ballif et al., 2012; Hum Genet 131:145–156; Nagamani et al., 2012; Eur J Hum Genet 20:176–179]. Taken together, our study reinforces the association between 1q43‐q44 CNVs and brain disorder. © 2016 Wiley Periodicals, Inc.